Modelos de simulação da ferrugem da folha do trigo : validação e impacto econômico - Mallmann, Guilherme (2009)
The wheat (Triticum aestivum L.) among the different crops, draft as one the most important humanity foods, being grown in the four corners of the world and a great economic and social relevance. Therefore, the yield wheat is very changed, is affected by many factors, as soil condition, environment conditions, management crop, among others. In some places, like Brazil, the incidence of many diseases is one of the most important factors that significantly contribute in the grain yield and quality loss. Among the fungal disease that limiting the yield wheat throughout the Brazil, there is the leaf rust caused by Puccinia triticina. The leaf rust is a major wheat disease in the world and common occurrence in southern Brazil. The disease develops readily when there is free moisture and temperature around 20°C. The successive generations of uredospores can be produced for each period of 10 to 14 days, if conditions are favorable, where the rain is often considered a factor leading in disease expansion, because the event rain is followed by an extended leaf wetness period, which is critical for infection process of leaf rust. The yield losses due leaf rust may reach 46% in crop wheat. In last decades, the mathematical modeling of disease in plants, for example, has been expanding very rapidly, contributing to integrated management. The simulation models from leaf rust epidemics is a useful tool to decision making in the disease management Thus, the objective this study was: 1) calibrate and validate the simulation CropSim-Wheat model coupled in a generic sub-module disease than simulate a leaf rust epidemic, and, 2) use this model to assess financial impact of genetic resistance to leaf rust wheat cultivars in Rio Grande do Sul state. The results showed than model simulated correctly the plant growth and leaf rust severity, indicating the efficiency with little epidemics and epidemics years in comparison with data observed in the field. The financial cost of genetic resistance on yield wheat was measured with the parameters change of infection efficiency and resistance host factor used by the model. This estimate pointed an average annual financial loss from 1979 to 2007 period of $ 130,667,070.10 for the use of a fully susceptible cultivar compared to a grown immune to the area sown to wheat in Rio Grande do Sul